Apparatus for monitoring the resistivity of the hydration of cement cured at high temperature. Issue 2 (4th March 2017) - Zhang, Wenhua; Zhang, Yunsheng
ABSTRACT: A resistivity apparatus was developed to investigate the early hydration processes of cementitious materials cured at elevated temperatures. The apparatus consists of a temperature control system, resistivity measurement system, and automatic data acquisition system. The temperature control of the resistivity apparatus was ±0.5°C. Three parallel measurements varied by approximately 5%, which shows that the apparatus was reliable and reproducible. By monitoring the electrical resistivity of fresh cement, the hydration process was characterized. The developed device may provide valuable insights into the mechanisms of cement hydration at high curing temperatures. In addition, increased curing temperature accelerates the setting process and strength development of the cement. However, high temperature has negative effects on compressive strength of the material.